1966
DOI: 10.1126/science.152.3723.780
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Studies of Submicrosomal Membranes from Liver of Normal and Phenobarbital-Treated Rats

Abstract: Rabbit antiserums were prepared against three submicrosomal fractions from liver of normal or phenobarbital-treated rats. The two membrane fractions originating from the rough- and smooth-surfaced endoplasmic reticulum were characterized by the same soluble antigens, with the exception of a highly basic coinponent present only in extracts of rough membranes. The third fraction, whose subcellular origin is unknown, was different. It contained at least two typical marker antigens not present in the other fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is possible that the short length of PB pretreatment in this study may have underestimated the induction effect on hydrolysis. Results from other studies have suggested that rat liver esterase induction by PB is dependent on the dose and duration of pretreatment, and that different inducers have different magnitudes of effect on esterase induction (Lundkvist and Perlmann, 1966; Schwark and Ecobichon, 1968; Nousiainen and Hanninen, 1981). Nevertheless, current data is insufficient to ascertain an inducible effect of EIAEDs on LEV hydrolysis, but such an effect still cannot be ruled out and could explain our findings.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that the short length of PB pretreatment in this study may have underestimated the induction effect on hydrolysis. Results from other studies have suggested that rat liver esterase induction by PB is dependent on the dose and duration of pretreatment, and that different inducers have different magnitudes of effect on esterase induction (Lundkvist and Perlmann, 1966; Schwark and Ecobichon, 1968; Nousiainen and Hanninen, 1981). Nevertheless, current data is insufficient to ascertain an inducible effect of EIAEDs on LEV hydrolysis, but such an effect still cannot be ruled out and could explain our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Phenobarbital is known to induce hepatic microsomal esterase activity and also to modulate the esterase pattern in the rat (19,20). Phenobarbital pretreatment of mice acted differently upon the esterase activity with regard to the phenyl-propionic esters than to the acetic esters: the former substantially increased and the latter decreased ( Table III).…”
Section: Discussionmentioning
confidence: 99%
“…The " h2 " proteins of liver were found in the cathodic region as 5 arcs, some of which were reduced, while others were not detectable in hepatoma. (Rossowski, Weinrander and Hierowski, 1963;Deckers, 1964; Stanislawski et al, 1964;Abelev, 1965;Baldwin, 1965;Hase and Mahin, 1965;Khramkova and Guelstein, 1965;Fritz, 1966;Kashkin, 1966;Kitagawa et al, 1966;Lundkvist and Perlmann, 1966;Takayanagi, 1966;Beloshapkina and Khramkova, 1967;Dufour et al, 1967;LeBouton, 1967; Nikolaev, Li and Mil'non, 1967;Salerno, Courcon and Grabar, 1967;Schwenke and Kujawa, 1967;Chordi et al, 1969; Szafarz, Yamamoto and Weisburger, 1969;Louis and Blunck, 1970 …”
mentioning
confidence: 99%